2016
DOI: 10.1111/jdv.13556
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rosacea in the general population of Germany and Russia – The RISE study

Abstract: BackgroundThere is an unmet need for general population‐based epidemiological data on rosacea based on contemporary diagnostic criteria and validated population survey methodology.ObjectiveTo evaluate the prevalence of rosacea in the general population of Germany and Russia.MethodsGeneral population screening was conducted in 9–10 cities per country to ensure adequate geographic representation. In Part I of this two‐phase study, screening of a representative sample of the general population (every fifth person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
3
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 23 publications
4
80
3
14
Order By: Relevance
“…In these studies, four reported the prevalence of erythematotelangiectatic rosacea among patients with rosacea to be 72–80% and that of papulopustular rosacea to be 18–28% . Furthermore, one of these studies reported 4% with phymatous rosacea and 6·5–8·0% with ocular rosacea. The last study found the prevalence of erythematotelangiectatic rosacea to be 45%, with papulopustular rosacea 49%, phymatous rosacea 4·8% and ocular rosacea 1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, four reported the prevalence of erythematotelangiectatic rosacea among patients with rosacea to be 72–80% and that of papulopustular rosacea to be 18–28% . Furthermore, one of these studies reported 4% with phymatous rosacea and 6·5–8·0% with ocular rosacea. The last study found the prevalence of erythematotelangiectatic rosacea to be 45%, with papulopustular rosacea 49%, phymatous rosacea 4·8% and ocular rosacea 1%.…”
Section: Resultsmentioning
confidence: 99%
“…These were three population‐based studies and two studies of dermatological outpatients . In these studies, four reported the prevalence of erythematotelangiectatic rosacea among patients with rosacea to be 72–80% and that of papulopustular rosacea to be 18–28% . Furthermore, one of these studies reported 4% with phymatous rosacea and 6·5–8·0% with ocular rosacea.…”
Section: Resultsmentioning
confidence: 99%
“…9 Rosacea prevalence is highest in Estonia, where prevalence has been estimated at about 22%, 2 and lowest in Tunisia (0.2%) 3 and in Ghana, where the prevalence is 0%. 9 Rosacea prevalence is highest in Estonia, where prevalence has been estimated at about 22%, 2 and lowest in Tunisia (0.2%) 3 and in Ghana, where the prevalence is 0%.…”
Section: Discussionmentioning
confidence: 95%
“…Population‐based data on the prevalence of skin diseases are generally rare. At an international population level, prevalence data are available for only a few selected skin conditions, such as atopic dermatitis (AD) (The International Study of Asthma and Allergies in Childhood) and itchy rashes, and a recently published study has reported on the prevalence of rosacea in Germany and Russia …”
mentioning
confidence: 99%